2018
DOI: 10.1111/aej.12279
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial efficacy of 0.5% peracetic acid and EDTA with passive ultrasonic or manual agitation in an Enterococcus faecalis biofilm model

Abstract: We compared the antimicrobial efficacy of EDTA and 0.5% peracetic acid (PAA), with manual agitation (MA) or passive ultrasonic irrigation (PUI) in an Enterococcus faecalis biofilm model. Fifty-five single-rooted human premolar teeth were chemo-mechanically prepared and inoculated with E. faecalis for biofilm formation. These were divided into five groups (n = 11): saline solution, PAA+MA, PAA+PUI, EDTA+MA and EDTA+PUI. Root canal sampling and scanning electron microscopy of the canal lumen and dentinal tubule … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
20
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 24 publications
3
20
0
1
Order By: Relevance
“…Hartmann et al (Hartmann et al, ) used an in vitro root canal model with E. faecalis biofilm to assess the antimicrobial efficacy of root canal irrigations; they reported that after 48‐hr incubation and three repeat washes with 1 ml Distilled water to remove floating bacteria, the SEM images revealed a large number of E. faecalis still attached to the root canal system in the distilled water subgroup of CNI group. In addition, the images indicated that in this model, the E. faecalis biofilm had good adhesion to the root canal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hartmann et al (Hartmann et al, ) used an in vitro root canal model with E. faecalis biofilm to assess the antimicrobial efficacy of root canal irrigations; they reported that after 48‐hr incubation and three repeat washes with 1 ml Distilled water to remove floating bacteria, the SEM images revealed a large number of E. faecalis still attached to the root canal system in the distilled water subgroup of CNI group. In addition, the images indicated that in this model, the E. faecalis biofilm had good adhesion to the root canal.…”
Section: Discussionmentioning
confidence: 99%
“…SEM can visualize the number and distribution of bacteria on the root‐canal surfaces, but has a disadvantage of inability to measure thickness of the biofilm since sample preparation in SEM involves a dehydration step that can cause shrinkage of the biofilm (Mohmmed et al, ). Moreover, SEM does not provide information of cell viability (Hartmann et al, ). In the present study, we used fluorescent microscopy to observe the live bacteria of biofilms, which enabled direct imaging of reduction of the biofilm without sample fixation (Mohammed, Vianna, Penny, Hilton, & Knowles, ).…”
Section: Discussionmentioning
confidence: 99%
“…A common disadvantage of in vivo and ex vivo research methods is that in a clinical situation a large number of different bacteria could be present, thus, the results obtained can only be transferred to a specific clinical condition to a limited extent. Ex vivo research models, either human or bovine teeth [ 6 , 7 , 9 , 14 , 25 ] are usually inoculated after sterilization and having attempted to standardize the investigation parameters. The advantage of these methodologies is that they resemble an in vivo situation.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, to standardize with the NaOCl control group, this procedure was repeated twice, and the solution in question was renewed (11). When EDTA is used in association with NaOCl (27), or ultrasonically activated, its erosive effect is accentuated (28). Though, in our experimental set-up, this purported damage appears not to interfere with the sealing ability of the root filling.…”
Section: Discussionmentioning
confidence: 64%